A novel optimal road layout model based on urban cloud data. Issue 1 (21st March 2021) - Niu, Lede; Xiong, Liran
The model in traditional methods is poor in stability, efficiency and accuracy in urban road layout. In order to solve those problems, an optimal road layout model based on urban cloud data is proposed in this paper. In this model, the hardware is supplemented by GIS application software and Arc GIS technology is adopted for integrated development mode; geographic information is processed according to urban cloud data. Starting from road layout, simulation software such as VISSIM and VISSUM is combined on the designed model for traffic data sharing and simulation decision; software is designed based on calibration processing of 3S optimal urban road layout model parameters and traffic data are collected for road layout design, and the optimal layout is extracted through the genetic algorithm. The experimental results show that the method has high stability and design efficiency.